Osmo‐protectants improve cotton yield by alleviating moisture stress under semi‐arid conditions. (19th January 2023) - Singh, Kulvir; Rathore, Pankaj; Mishra, Sudhir Kumar
Abstract: In north‐western India, short‐term droughts due to insufficient rainfall or irrigation canal closures are common. To quantify seed cotton yield (SCY) loss under moisture deficit and evaluate the efficacy of foliar‐applied osmo‐protectants (OPs), a 2‐year field experiment was conducted with three moisture regimes (M1 : well watered, M2 : rainfed after single post‐sowing irrigation [POSI], and M3 : rainfed after two POSIs) in main plots and eight OPs (S1 : control, S2 : four sprays of 2% urea at weekly intervals, S3 : four sprays of 2% KNO3 at weekly intervals, S4 : single spray of 500 mg kg −1 thio urea [TU], S5 : single spray of 50 mg kg −1 salicylic acid [SA], S6 : single spray of 100 mg kg −1 glycine betaine [GB], S7 : single spray of 100 mg kg −1 SA, and S8 : three sprays of 1% pink pigmented facultative methylobacteria at 10 days interval) in sub‐plots of a split plot design. Moisture stress induced a reduction of relative water content (RWC) and consequently decreased SCY by 17% and 32.9% under M3 (2821 kg ha −1 ) and M2 (2291 kg ha −1 ), respectively, compared to M1 (3418 kg ha −1 ). Except for TU, all tested OPs improved SCY by 6.3%–23.7% in comparison to the nontreated control. Application of SA and GB enhanced photosynthesis, improved stomatal conductance, and maintained higher RWC. Application of SA at 100 mg kg −1 resulted in an additional income of US458 ha −1 and was the most economical treatment for countering short‐term drought. Core Ideas: Exogenous application of osmo‐protectants (OPs) is beneficial under arid environments. Improved physiological and yield attributes enhanced yield under water stress. OP application improved cotton yield by 6.3%–23.7% over control. Salicylic acid and glycine betaine proved better in minimizing yield loss.